Pokok-Pokok Ajaran Syi’ah - A, Arlan; Santalia, Indo (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
A variety of literature explains the emergence of Shia. The teachings in Shia are very many and different, so we must seek and know the teachings, doctrines, and figures who have a big impact on this group. In addition, in this Shia sect there are many parts and differences of opinion in belief. Which is marked by the emergence of several sects such as Kaisaniyah, Zaidiyah, Imamiyah, and Kaum Gulat. This requires us to always be careful and anticipate the existence of harsh doctrines that may develop, or have even been so rapid in spreading their teachings to countries with a majority Muslim population, such as in Indonesia. One of them is stating that Ali bin Abu Thalib is the most important among the companions and is more entitled to hold the leadership of the Muslims. Even worse are those who worship and consider that Ali bin Abi Thalib is not an ordinary human being, but an incarnation of God or even God himself.